The Tunka Radio Extension: Latest Analysis Results. (July 2015) - Kostunin, D; Bezyazeekov, P A; Budnev, N M; Gress, O A; Haungs, A; Hiller, R; Huege, T; Kazarina, Y; Kleifges, M; Konstantinov, E N; Korosteleva, E E; Krömer, O; et al.
Abstract: Tunka-133 is an air-Cherenkov array placed in Siberia, near the southern tip of Lake Baikal, which registers air showers induced by cosmic rays from initial particles with energies of 10 16 -10 18 eV. After several years of successful data collection, this array was extended by other detector arrays. One of them is the Tunka Radio Extension (Tunka-Rex): the radio array consists of presently 25 antenna stations connected to the data acquisition of Tunka-133. This combination provides hybrid measurements and the possibility for cross-calibration between the air-Cherenkov and radio measurement techniques. The main goal of Tunka-Rex is to determine the precision of the reconstruction of air-shower parameters using the radio detection technique. We present the latest results on the event reconstruction.